1997
DOI: 10.1023/a:1009689804217
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: An efficient method for the solid phase synthesis of allylic alcohols via the Baylis-Hillman reaction has been developed. In the presence of DABCO or 3-quinuclidinol the coupling of resin bound acrylic acid with different aldehydes yields allylic alcohols. Aldehydes with different reactivity were used and gave modest to excellent yields upon simply varying the base or the reaction time. The allylic alcohols were reacted with primary amines to form 1,3-aminoalcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…They also examined the application of resin-bound acrylate in performing the Baylis−Hillman reaction with various aldehydes. The resulting products were converted into the amino alcohols via the treatment with amines (Scheme ) 20 …”
Section: Amine-catalyzed Baylis−hillman Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also examined the application of resin-bound acrylate in performing the Baylis−Hillman reaction with various aldehydes. The resulting products were converted into the amino alcohols via the treatment with amines (Scheme ) 20 …”
Section: Amine-catalyzed Baylis−hillman Reactionmentioning
confidence: 99%
“…The resulting products were converted into the amino alcohols via the treatment with amines (Scheme 20). 111 Kunzer and co-workers 112 described the Baylis-Hillman reaction on solid support and utilized these Very recently, Aggarwal and co-workers 116 examined the correlation between pK a of a variety of quinuclidine-based catalysts (Figure 2) and their reactivities in the Baylis-Hillman reaction. They found that quinuclidine in protic solvents has the highest pK a (11.3/H 2 O) and is the most active catalyst for this reaction.…”
Section: Essential Componentssdevelopmentsmentioning
confidence: 99%
“…One example of the Baylis-Hillman reaction was used in the solid-phase synthesis of amino alcohols. 87 In this SPOS, the starting polymer-bound acrylate was created on 2-chlorotrityl chloride resin (Scheme 68). Optimization of the Baylis-Hillman reaction established that 3-hydroxyquinuclidine (3-HQN) performed better overall on a variety of aldehydes than 1,4-diazabicyclo[2.2.2]-octane (DABCO).…”
Section: Baylis−hillman Reactionmentioning
confidence: 99%
“…In an earlier observation, Li et al too have reported 40 the formation of an unidentified side product (10%) during the TiCl 4 -mediated BH reaction of p -nitrobenzaldehyde and α, β-cycloalkenone. In the studies directed toward the BH reaction of 5-isoxazolecarboxaldehydes we have earlier reported that these substrates undergo fast reaction both in solution phase 29 and on solid support 31d. In our continued work in this area we have also carried out the BH reaction with α,β-unsaturated cyclic ketones in the presence of TiCl 4 .…”
Section: Introductionmentioning
confidence: 97%